Phosphorylation of Spastin Promotes the Surface Delivery and Synaptic Function of AMPA Receptors - Chen, Li; Wang, Hanjie; Cha, Shuhan; Li, Jiong; Zhang, Jiaqi; Wu, Jiaming; Guo, Guoqing; Zhang, Jifeng (Frontiers in Cellular Neuroscience, 2022)
Synaptic plasticity is essential for cognitive functions such as learning and memory. One of the mechanisms involved in synaptic plasticity is the dynamic delivery of AMPA receptors (AMPARs) in and out of synapses. Mutations of SPAST, which encodes SPASTIN, a microtubule-severing protein, are considered the most common cause of hereditary spastic paraparesis (HSP). In some cases, patients with HSP also manifest cognitive impairment. In addition, mice with Spastin depletion exhibit working and associative memory deficits and reduced AMPAR levels. However, the exact effect and molecular mechanism of Spastin on AMPARs trafficking has remained unclear. Here, we report that Spastin interacts with AMPAR and phosphorylation of Spastin enhances its interaction with AMPAR subunit GluA2. Further study shows that phosphorylation of Spastin can increase AMPAR GluA2 surface expression and the amplitude and frequency of miniature excitatory synaptic currents (mEPSC) in cultured hippocampal neurons. Moreover, phosphorylation of Spastin at Ser210 is crucial for GluA2 surface expression. Phosphorylation of Spastin K353A, which obliterates microtubule-severing activity, also promotes AMPAR GluA2 subunit trafficking to the surface and increases the amplitude and frequency of mEPSCs in cultured neurons. Taken together, our data demonstrates that Spastin phosphorylation promotes the surface delivery of AMPAR GluA2 subunit independent of microtubule dynamics.